Legal Protection of the Rights of Pregnant Women Prisoners in Lubuk Pakam Correctional Institution - Binsar Reski Simamora; Fitri Ramadhani Siregar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The rights of female prisoners must be considered specifically for female prisoners, because every woman experiences menstruation, pregnancy, childbirth and breastfeeding. Coaching in correctional institutions must pay attention to laws governing special rights for women prisoners. This research is normative juridical and empirical juridical research, so the approach taken is a statutory approach, because what will be studied are various legal rules that become the focus and central theme of a study. The research specification used is descriptive analysis, namely describing the results of research with complete data and as detailed as possible. Description is intended for primary, secondary and tertiary data related to legal protection of women prisoners through analysis using relevant laws and theories. Based on the Law of the Republic of Indonesia Number 22 of 2022 concerning Corrections Article 9 Paragraph (4). Prisoners who are entitled to health services and proper food in accordance with nutritional needs, while based on Government Regulation Number 32 of 1999 concerning Terms and Procedures related to the Implementation of the Rights of Prisoners, Article 20 Paragraph (1) Prisoners and Correctional students who are sick, pregnant or breastfeeding are entitled to additional food in accordance with the doctor's instructions, but the reality in the prison is not like that, there is no assertiveness from the prison towards providing the rights of pregnant women, so that the implementation becomes ineffective.